Beyond the limits of clinical governance? The case of mental health in English primary care - Campbell Stephen; Rogers Anne; Gask Linda; Sheaff Rod (BMC, 2008)
Abstract Background Little research attention has been given to attempts to implement organisational initiatives to improve quality of care for mental health care, where there is a high level of indeterminacy and clinical judgements are often contestable. This paper explores recent efforts made at an organisational level in England to improve the quality of primary care for people with mental health problems through the new institutional processes of 'clinical governance'. Methods Framework analysis, based on the Normalisation Process Model (NPM), of attempts over a five year period to develop clinical governance for primary mental health services in Primary Care Trusts (PCTs). The data come from a longitudinal qualitative multiple case-study approach in a purposive sample of 12 PCTs, chosen to reflect a maximum variety of organisational contexts for mental health care provision. Results The constant change within the English NHS provided a difficult context in which to attempt to implement 'clinical governance' or, indeed, to reconstruct primary mental health care. In the absence of clear evidence or direct guidance about what 'primary mental health care' should be, and a lack of actors with the power or skills to set about realising it, the actors in 'clinical governance' had little shared knowledge or understanding of their role in improving the quality of mental health care. There was a lack of ownership of 'mental health' as an integral, normalised part of primary care. Conclusion Despite some achievements in regard to monitoring and standardisation of prescribing practice, mental health care in primary care seems to have so far largely eluded the gaze of 'clinical governance'. Clinical governance in English primary mental health care has not yet become normalised. We make some policy recommendations which we consider would assist in the process normalisation and suggest other contexts to which our findings might apply.